"Post-Stroke Aphasia: A Psycholinguistic Approach to Speech Disorder Identification" - Muin, Fadhliyah Rahmah; Cinta Lembang (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study aims to identify changes in the way individuals speak after a stroke based on psycholinguistic studies. The methods used to obtain information are descriptive qualitative and literature review. Information was obtained from interviews with respondents who had had a stroke. The respondent is a woman and she is 55 years old. The results showed that there were many changes experienced by individuals both in terms of physical social and emotional after a stroke. The most significant change is in the way individuals speak. Damage to the brain causes the patient to experience a stroke and its implications for other body nerves. One of them is speech disorders (speech aphasia). In conclusion, the brain and language influence each other both in processing language, acquiring language and understanding language. Therefore, if there is damage to the brain, it is difficult or even impossible for humans to process, produce and understand a language.